A cognitive poetic model of humour in fiction - Haines, Alice (2019)
This thesis proposes a cognitive poetic model of discoursal humour: the 3D Model of Humour. Previous research has tended to separate aspects of humour in terms of the affective experience it produces, its cognitive basis, or its social inclusion and exclusion effects. However, humour is an integrated form of discourse and the context is a crucial part of how participants interpret a text. This thesis claims that the cognitive process of recognising humour is the basis of the elicitation of the affective state of humour appreciation. The aim of the 3D Model is, therefore, to integrate the findings of the various approaches to provide an account of humour that can explain how the recognition of humour can lead to the affective state of humour appreciation, and how recognition and appreciation relate to the social context and effects.